Wien im Jahre 1703 Die Vogelschau des Dessauer Gesandten Bernhard Georg Andermüller und die Transformation des Wiener Stadtbildes - Scheutz, Martin (2018)
Bernhard Georg Andermüller (1644-1717), envoy of Dessau, and Michel Herstal de la Tache drew fascinating maps/plans of early modern Vienna. We see on the one hand the working environments of an early modern envoy on these plan but also the fortification of the town and the suburbs around 1700 can still be clearly felt.